From here to maternity : becoming a mother - Oakley, Ann (Policy Press, 2018)
Ann Oakley is a pioneer in the field of sociological research. In this classic re-issue, she interviewed 60 women to find out what it's really like to have a baby. Covering pregnancy, birth and child care, she relies on the stories mothers tell to discuss whether and why women want to become pregnant, how they imagine motherhood to be, the experience of birth, post-natal depression, feeding and caring routines and the challenges for the domestic division of labour and to fathers. She shows that most women are unprepared for the birth or the work of caring for a baby, but also for the joys that a baby can bring. As topical today as the day it was written, this important book was the first to examine first-time motherhood in the words of those experiencing it, and it continues to influence generations of researchers today.